2006
DOI: 10.1080/14616730600856131
|View full text |Cite
|
Sign up to set email alerts
|

Maternal secure base scripts, children's attachment security, and mother – child narrative styles

Abstract: This paper reports the results of a study examining links between maternal representations of attachment, child attachment security, and mother and child narrative styles assessed in the context of reminiscences about shared experiences. Participants were 90 mother - child dyads. Child attachment security was assessed using the attachment Q-set and maternal attachment representations were measured using a recently designed instrument that assesses the script-like qualities of those representations. Analyses ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 45 publications
11
79
0
13
Order By: Relevance
“…In a study of associations among attachment variables and mother-child reminiscences concerning emotionally charged events in the child's life, Bost et al (2006) found that the mother's scriptedness score was positively associated with child participation and with the use of emotion words by both mother and child. These results are consistent with the notion that the secure base script includes awareness and regulation of affect .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of associations among attachment variables and mother-child reminiscences concerning emotionally charged events in the child's life, Bost et al (2006) found that the mother's scriptedness score was positively associated with child participation and with the use of emotion words by both mother and child. These results are consistent with the notion that the secure base script includes awareness and regulation of affect .…”
Section: Introductionmentioning
confidence: 99%
“…Assim, de forma a controlar efeitos decorrentes da extensão do discurso foi realizada uma proporção para cada categoria em relação ao número de palavras do discurso, dividiu-se o valor de cada categoria de cada sujeito (mãe, pai e criança) pelo número de palavras do seu discurso, multiplicou-se por 100 e obtiveram-se assim proporções para cada categoria discursiva (e.g., Bost et al, 2006). …”
Section: Resultsunclassified
“…Depois de devidamente codificadas, omitindo informações da criança e dos pais, todas as transcrições foram analisadas por dois investigadores independentes, previamente treinados, relativamente às características do discurso da criança e do adulto (para exemplos ver Bost et al, 2006;Farrant & Reese, 2000;Fivush & Fromhoff, 1988;. (Fivush & Fromhoff, 1988), todas as transcrições foram marcadas com o início e fim em relação aos três eventos falados.…”
Section: Procedimentounclassified
See 2 more Smart Citations